G Protein-Coupled Receptors: Undervalued Targets for Cancer Therapy - Al-Janabi, Ismail Ibrahim (Iraqi Journal of Pharmaceutical Sciences, 2022)
Despite the G protein-coupled receptors (GPCRs) being the largest family of signalling proteins at the surface of cells, their potential to be targeted in cancer therapy is still under-utilised. This review highlights the contribution of these receptors to the process of oncogenesis and points to some likely challenges that might be encountered in targeting them. GPCR-signalling pathways are often complex and can be tissue-specific. Cancer cells hijack these communication networks to their proliferative advantage. The role of selected GPCRs in the different hallmarks of cancer is examined to highlight the complexity of targeting these receptors for therapeutic benefit. Our increasing knowledge of the mechanisms governing the molecular functions of GPCRs may help to identify new targets to treat specific types of cancers.